2022
DOI: 10.1155/2022/4008966
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Buqi Huoxue Decoction Combined with Cardiac Rehabilitation Nursing after Coronary Intervention in Patients with Acute ST-Segment Elevation Myocardial Infarction and Its Influence on Prognosis

Abstract: Objective. To investigate the efficacy of the application of Buqi Huoxue Decoction combined with cardiac rehabilitation nursing for patients with acute ST-segment elevation myocardial infarction (STEMI) after percutaneous coronary intervention (PCI) and its influence on the prognosis. Methods. 120 STEMI patients undergoing PCI were randomly divided into control group, cardiac care group, traditional Chinese medicine and western medicine group (TCM + WM group), and comprehensive treatment group. The control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Several studies have established that the combination of conventional western medicine with Chinese herbal medicine can not only further improve clinical symptoms but also lower the incidence of long-term MACEs. [ 13 , 26 ] In this study, the efficacy and safety of acupuncture combined with XFZYD for the treatment of MACEs after PCI are systematically evaluated so as to provide evidence-based medical guidance for this application in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have established that the combination of conventional western medicine with Chinese herbal medicine can not only further improve clinical symptoms but also lower the incidence of long-term MACEs. [ 13 , 26 ] In this study, the efficacy and safety of acupuncture combined with XFZYD for the treatment of MACEs after PCI are systematically evaluated so as to provide evidence-based medical guidance for this application in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%